The Effect Of Work Discipline And Motivation On Performance Employees In The Police Civil Service Unit Of Karawang Regency - Muhajirin; Budi Rismayadi; Wike Pertiwi (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — he research aims to determine employee performance which can be influenced simultaneously and partially by the work discipline and motivation of the Karawang Regency Satpol PP.Research method— he population in this study was 108 employees who had a tolerable error rate of 10% or an accuracy rate of 90%. Therefore, a purposive cluster probability sampling technique was used to sample 52 employees to represent the population. Descriptive and verification methods are used in this research, which means collecting data, displaying, analyzing and testing hypotheses, before making conclusions and recommendations. Descriptive statistical analysis, classical assumption tests, and multiple linear regression analysis were used with SPSS 26 hypothesis testing.Result— This research results that employee performance can be partially significantly and positively influenced by work discipline, employee performance can be partially significantly and positively influenced by work motivation, Employee performance can be affected simultaneously by discipline and work motivation.Conclusion— The work discipline and motivation of employees in the Karawang Regency Satpol PP have a significant and positive effect on employee performance, both partially and simultaneously.